Rancang Bangun Sistem Informasi Eksekutif Dashboard Monitoring Produksi Pada PT. Perkebunan Nusantara VI - Ahad, Syahdi Zul; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2022)
Design and build a production monitoring dashboard executive information system as a strategic step for the Board of Management (BOM) in making decisions. This study aims to assist the Executive management of PT. Perkebunan Nusantara VI can get information faster and more accurately. The information is in the form of production results, losis, restan and so on in the business unit, and in this study it is only limited to the production of Palm Oil Mills (PKS) and the production of Palm Oil plants. This research was developed with the development model Waterfall and then implemented into the application. The results of this assessment are the Production Monitoring Dashboard Executive Information System (SIEDASI) at PT. Perkebunan Nusantara VI Web-based.